The effect of p-aminosalicyclic acid on iron transport and assimilation in mycobacteria - Brown, Keith A.; Ratledge, Colin (Biochimica et biophysica acta, 1975)
p-Aminosalicylic acid inhibits growth of Mycobacterium bovis BCG and Mycobacterium smegmatis more effectively if cells are growing with a sufficiency of iron (> 1 μg Fe/ml) in the medium than if cells are deficient in iron (<0.1 μg Fe/ml). In iron-deficient cultures formation of mycobactin, an ionophore for iron transport, is strongly inhibited by p-aminosalicylic acid. Uptake of iron into cell suspensions is also inhibited and the activity of several iron-containing enzymes declines in cells exposed to p-aminosalicylic acid during their growth. p-Aminosalicylic acid is about 50 times more effective towards a mutant of M. smegmatis which required mycobactin under iron-deficient growth conditions than towards the wild-type parent. p-Aminosalicylate is taken up into cells by an active process independent of the salicylate uptake system, possibly by the route used for assimilation of p-aminobenzoate. (This could account for why p-aminobenzoic acid, but not salicylic acid, antagonizes the action of p-aminosalicylic acid.) With iron-deficient cells, salicylate assimilation is about 50 times greater than either p-aminosalicylate or p-aminobenzoate but with iron-sufficient cells and with the mycobactin mutant salicylate uptake is negligible whereas p-aminobenzoate and p-aminosalicylate uptakes are unaffected. p-Aminosalicylic acid at 3.3 mM (500 μg/ml) partially inhibits the uptake of both p-aminobenzoate and, if it is occuring, that of salicylate as well. As p-aminosalicylic acid is always more effective when the intracellular concentration of salicylic acid is low, it probably acts as an anti-metabolite of salicylic acid, not, however, by inhibiting the conversion of salicylic acid to mycobactic, but probably somewhere along the metabolic pathway of iron uptake.